Peygamberimizin Kur’an’dan iktibasları - Tok, Fatih (My University, 2005)
The aim of this thesis is to learn how the Prophet adapted Koran to his daily life and to learn what the meaning of Koran for his life is. To do this, we have examined the Prophet's quotations from Koran during his speeches, homilies, and daily talks. We've studied the subject of 'quotation' in literature books and the Prophet's quotations from Koran in Hadith books. As a result, we have realized that all what the Prophet says and does refers to Koran. In some cases he also explained to which verse of Koran his acts and words refer. By studying the Prophet's quotations from Koran, we have tried to demonstrate how Koran's verses are applicable to daily life. TEZ ÖZETİ Tezin amacı, Peygamberimizin Kur'an'ı günlük hayatına nasıl aktardığını ve Kur'an'ın onun hayatında ne anlam ifade ettiğini öğrenmekti. Bunun için Peygamberimizin hitabelerinde, vaazlarında, günlük konuşmalarında Kur'an'dan yaptığı iktibasları inceledik. İktibas konusunu edebiyat kitaplarından, Peygamberimizin Kur'an'dan İktibaslarını da Hadis kitaplarından araştırdık. Çalışmamızın sonunda gördük ki, Peygamberimizin söylediği her söz ve yaptığı her davranış Kur'an' dayanıyor. Bazı durumlarda ise söylediklerinin ve yaptıklarının Kur'an'dan hangi ayete dayandığını iktibas yaparak ortaya koymuştur. Biz de bu tezimizde iktibasları inceleyerek Kur'an'ın hayatın içine nasıl aktarıldığını ortaya koyduk.
Keywords: Din; İslam Dini; Kur’an ve Kur’an İlimleri; Kur’an_Tefsir